GLUCOSE LEVELS IN LATE PRETERM AND TERM NEWBORNS AT ONE HOUR OF LIFE AND FREQUENCY OF HYPOGLYCEMIA: Glucose Levels in Late Preterm and Term Newborns - Afzal, Muhammad; Yaqoob, Asma; Afzal, Alizay Gohar; khan, Kashmala; Wahab, Abdul (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine glucose levels in late preterm and term newborns at one hour of life in our population, along with the frequency of symptomatic hypoglycemia and it’s known risk factors. Study Design: Descriptive study Place and Duration of Study: Quaid-e-Azam International Hospital (QIH) Islamabad from July 2012 to September 2013. Material and Methods: Two hundred and seventy newborns were selected by consecutive purposive non probability sampling who were born at QIH either by spontaneous vaginal delivery or cesarean section. Only healthy neonates were included. Gestational age, weight, fetal and maternal risk factors were assessed. Glucose level was measured by glucometer at 1 hour of life after first feed. Neonates that became symptomatic with low glucose levels were thoroughly studied, readings reconfirmed from laboratory and were promptly managed. Results: Thirty (11%) babies showed sugar level < 30 mg/dl at 1 hour of life. Out of them 18(60%) were late preterm and 12(40%) were term babies. Out of them 12(40%) babies weighed <2kg, 8(26%) were between 2-2.5 kg and 6(20%) were 2.5-4.0 kg while 4(14%) babies were between 4.0 to 4.6 kg. Only 6(2.2%) newborns became symptomatic with low sugar level. Among symptomatic newnates, 4 mothers had gestational diabetes and other two were with pregnancy induced hypertension (PIH). Important risk factors were gestational diabetes, PIH, fetal distress and SGA babies. Safest lower glucose level was found to be 30 mg/dl at 1 hour after birth. Conclusion: Plasma glucose levels measured at 1 hour of life in late preterm and term newborns in our population are consistent with international studies. Frequency of symptomatic hypoglycemia is quite low and normal newborns without risk factors do not need screening. However one needs to be vigilant in babies with risk factors.